Konstruksi Wacana Moderasi Beragama di Ruang Digital (Studi Kasus Konten Bertema Toleransi di Media Sosial Youtube) - Musahwi; Minati Zulfa Anika; Pitriyani (UIN Siber Syekh Nurjati Cirebon, 2023)
This article will analyze the construction of religious moderation through various digital channels on YouTube. YouTube is the most popular social media platform in Indonesia, with 94% of social media users choosing to access YouTube compared to other social media platforms, based on the 2022 Populix survey. While religious moderation has been politically legitimized through the Ministry of Religious Affairs and various institutional policies, it often faces opposition from opposing groups referred to as intolerant and radical ideologies, causing religion to be seen in two completely different frames: as a weapon of control that promotes diversity, and on the opposing side, as a counter attack for delegitimize power. Therefore, it is interesting to examine the construction of religious moderation through the YouTube social media platform. Framing analysis is chosen to gain a clearer understanding of the structure of religious moderation as a message intentionally constructed for the public. There are 3 YouTube channels examined: Deddy Corbuzier, Noice, and Jeda Nulis, based on the number of viewers, subscribers, and comments on each account. Based on the analysis, several frames are constructed: 1) the younger generation and their respect for the community and religion; 2) different but together; and 3) Indonesia as a shared home